ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN PROJECT KREATIF DAN KEWIRAUSAHAAN DI SMK NEGERI 10 MERANGIN - Khoirina Fidianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the learning interests of eleventh-grade students in the creative projects and entrepreneurship subjects at SMK Negeri 10 Merangin. The study used Classroom Action Research (CAR). Twenty-one students participated in the study. Data collection was conducted through direct observation and interviews with the eleventh-grade students, the creative projects and entrepreneurship subject teachers, and the homeroom teachers. The findings revealed that only students who were interested in the subject enjoyed the creative projects and entrepreneurship lessons. 75% of students disliked the theory because they found it boring and only enjoyed group work and practical exercises. When the teacher gave assignments, students submitted them late. 83% of students did not pay attention to the teacher's explanations in class, and on average, students did not take notes; they only took notes when instructed to do so. 75% of students still lacked confidence and were afraid to express their opinions in class.